Espejos : una historia casi universal - Galeano, Eduardo, 1940-2015 (Biblioteca Eduardo Galeano., 2008)
The unofficial history of the world seen--and mirrored to us--through the eyes and voices of history's unseen, unheard, and forgotten, over 5000 years of history.